2007
DOI: 10.1037/0012-1649.43.2.454
|View full text |Cite
|
Sign up to set email alerts
|

Lexical exposure and word-form encoding in 1.5-year-olds.

Abstract: In this study, 1.5-year-olds were taught a novel word. Some children were familiarized with the word's phonological form before learning the word's meaning. Fidelity of phonological encoding was tested in a picture-fixation task using correctly pronounced and mispronounced stimuli. Only children with additional exposure in familiarization showed reduced recognition performance given slight mispronunciations relative to correct pronunciations; children with fewer exposures did not. Mathematical modeling of voca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
100
3

Year Published

2008
2008
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 93 publications
(106 citation statements)
references
References 76 publications
3
100
3
Order By: Relevance
“…Though Maye et al (2002) showed that short-term modification of infants' speech categories is possible with very little training, it remains the case that infants' day-to-day exposure to speech dwarfs the 440 stimuli our participants listened to. Indeed, American infants hear between 500 and 1,500 words spoken to them by their parents each hour they interact (Hart & Risley, 1995, p. 239; see also Swingley, 2007). The everyday speech input infants receive, on the other hand, is much more complex in terms of contextual variability and talker characteristics than our stimuli.…”
Section: Discussionmentioning
confidence: 98%
“…Though Maye et al (2002) showed that short-term modification of infants' speech categories is possible with very little training, it remains the case that infants' day-to-day exposure to speech dwarfs the 440 stimuli our participants listened to. Indeed, American infants hear between 500 and 1,500 words spoken to them by their parents each hour they interact (Hart & Risley, 1995, p. 239; see also Swingley, 2007). The everyday speech input infants receive, on the other hand, is much more complex in terms of contextual variability and talker characteristics than our stimuli.…”
Section: Discussionmentioning
confidence: 98%
“…Although this may seem unrealistically high, the input to the model is miniscule compared to the language that humans are exposed to during childhood and adulthood. For example, even pre-literate infants may be exposed to as many as half a million words in just a 3 week period (Swingley, 2007).…”
Section: Chunk Learningmentioning
confidence: 99%
“…This stands in contrast with ERP studies, and adult experiments generally, where a fixation stimulus is systematically presented to centre the participant's attention before trial onset (Kuipers & Thierry, 2011). When a central fixation point is used, trials are always triggered by the experimenter, but not systematically when such cue is not used, in which case trials are sometimes automatically interspaced (Ramon-Casas et al, 2009;Swingley, 2003Swingley, , 2007.…”
Section: Central Fixation Pointmentioning
confidence: 91%
“…Indeed, whereas the Switch task is designed for novel word learning situations, the IPL allows for the investigation of novel word learning (e.g., Gurteen, Horne, & Erjavec, 2011;Schafer & Plunkett, 1998;Swingley & Aslin, 2002, 2007 together with familiar word recognition (e.g., Fernald, Pinto, Swingley, Weinberg, & McRoberts, 1998;Fernald et al, 2008;Houston-Price, Mather, & Sakkalou, 2007;Mani, Coleman, & Plunkett, 2008;Mani & Plunkett, 2007, 2011aRamon-Casas, Swingley, Sebastián-Gallés, & Bosch, 2009;White & Morgan, 2008), mutual exclusivity (Houston-Price, Caloghiris, & Raviglione, 2010) and most recently has been adapted for priming tasks (e.g., Arias-Trejo & Plunkett, 2009, 2013Mani, Durrant, & Floccia, 2012;Styles & Plunkett, 2009).…”
Section: Introductionmentioning
confidence: 99%